Design, synthesis and biological evaluation of 6-aryl-1, 6-dihydro-1, 3, 5-triazine-2, 4-diamines as antiplasmodial antifolates. Issue 33 (1st August 2016) - Lourens, Anna C. U.; Gravestock, David; van Zyl, Robyn L.; Hoppe, Heinrich C.; Kolesnikova, Natasha; Taweechai, Supannee; Yuthavong, Yongyuth; Kamchonwongpaisan, Sumalee; Rousseau, Amanda L.
Abstract : One-pot multistep synthesis of 1, 6-dihydro-1, 3, 5-triazines displaying potent antiplasmodial activity in vitro . Abstract : The design, synthesis and biological evaluation of a series of 6-aryl-1, 6-dihydro-1, 3, 5-triazine-2, 4-diamines is described. These compounds exhibited in vitro antiplasmodial activity in the low nanomolar range against both drug sensitive and drug resistant strains of P. falciparum, with 1-(3-(2, 4-dichlorophenoxy)propyl)-6-phenyl-1, 6-dihydro-1, 3, 5-triazine-2, 4-diamine hydrochloride identified as the most potent compound from this series against the drug resistant FCR-3 strain (IC50 2.66 nM). The compounds were not toxic to mammalian cells at therapeutic concentrations and were shown to be inhibitors of parasitic DHFR in a biochemical enzyme assay.